Caturdaśalakṣaṇī Gādādharī : vyākhyāyatrayayutā - Gaṅgeśa, 13th cent (Adyar Library series, 1942)
Portion of a supercommentary on Tattvacintamanididhiti by Raghunatha Siromani, 16th century commentary on Tattvacintamani, 13th century basic neo-Nyaya work, by Gangesa.